Variability of ecological and autotrophic host specificity in a mycoheterotrophic system: Pterospora andromedea and associated fungal and conifer hosts. (April 2016) - Dowie, Nicholas J.; Grubisha, Lisa C.; Trowbridge, Steven M.; Klooster, Matthew R.; Miller, Steven L.
Abstract: Few studies of tripartite mycoheterotrophic systems have examined ecological specificity across broad geographic ranges or addressed autotrophic host specificity. Pterospora andromedea was selected as an ideal candidate to examine ecological specificity of a mycoheterotrophic system as it is widely distributed, has been shown to have high levels of symbiont specificity with Rhizopogon subgenus Amylopogon, and is found with several autotrophic hosts. Pairs of P. andromedea + Rhizopogon spp. samples were co-collected across North America and were sequenced using trnL and ITS, respectively. Bayesian phylogenetic reconstructions between the co-collected taxa were used to examine ecological specificity, and for subsequent tests for autotroph specificity. P. andromedea lineages exhibited both high specificity and relaxed specificity for fungal symbionts and autotrophic hosts across the geographic landscape under allopatric and sympatric conditions. This strong evidence for geographic mosaics of specificity in mycoheterotrophic systems is an important future consideration in determining the evolutionary ecology of mycoheterotrophs.